KONTRIBUSI PENDAPATAN GULA MERAH TERHADAP PENDAPATAN KELUARGA PETANI KELAPA SAWIT DI DESA KERTAMUKTI KECAMATAN AIR SUGIHAN KABUPATEN OGAN KOMERING ILIR - Hardiansyah, Firman; Batubara, Mustopa Marli (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2021)
The purpose of this study was to find out how much income and income contribution from the brown sugar business to the household farmer’s oil palm income in Kertamukti Village, Air Sugihan District, Ogan Komering Ilir Regency in April 2021. The research method used was a survey, for the sampling method used. is the census method or saturated sample, the data collection method used is interviews and data processing in this study using quantitative analysis methods. From the research results, the average production obtained from oil palm farming is 4,025 Kg per month, in Kertamukti Village, Air Sugihan District, Ogan Komering Ilir Regency and the average income obtained from oil palm farming is Rp. 5,404,027 per month. Coconut farming income is Rp. 639,980 and from the results of the average brown sugar processing business is 93.75 Kg per month while the income is Rp. 1,922,974 per month. So, from the average income above, the family income is Rp. 8,016,980 per month, and the contribution of the brown sugar business to the family income of oil palm farming is 23.90%.